Emerging technologies of augmented reality interfaces and design - Haller, Michael; Billinghurst, Mark; Thomas, Bruce (Idea Group Publishing, 2007)
"This book provides a good grounding of the main concepts and terminology for Augmented Reality (AR), with an emphasis on practical AR techniques (from tracking-algorithms to design principles for AR interfaces). The targeted audience is computer-literate readers who wish to gain an initial understanding of this exciting and emerging technology" - Provided by publisher
Includes bibliographical references and index
Keywords: Human-computer interaction; Virtual reality; User interfaces (Computer systems); Erweiterte Realität -- Informatik; Aufsatzsammlung